The end of cinema? A medium in crisis in the digital age - Gaudreault, André 1952-; Marion, Philippe (Film and culture, 2015)
Introduction: The end of cinema? -- Cinema is not what it used to be -- Digitalizing cinema from top to bottom -- A brief phenomenology of 'digitalized' cinema -- From shooting to filming: the Aufhebung effect -- A medium is always born twice -- New variants of the moving image -- 'Animage' and the new visual culture -- Conclusion: A medium in crisis in the digital age